Energy storage in metal cobaltite electrodes: Opportunities & challenges in magnesium cobalt oxide. (May 2021) - Krishnan, Syam G.; Arulraj, Arunachalam; Khalid, Mohammad; Reddy, M.V.; Jose, Rajan
Abstract: Ternary metal cobaltites (TMCs) offering high charge storability, multiple oxidation states, and improved electrical conductivity are widely explored as electrodes for energy storage devices. Among them, magnesium cobalt oxide or magnesium cobaltite (MgCo2 O4 ) could be a cheaper analogue due to the abundance of magnesium; however, limited by materials stability in certain electrolytic conditions, formation of insulating layers hindering the charge response under charge/discharge conditions. While certain morphologies of MgCo2 O4 delivered capacities higher than the theoretical capacity in lithium ion storage mode, it delivered only a quarter of the theoretical value in a supercapattery storage mode. This review critically analyzes the progress in MgCo2 O4 as a charge storing electrode for lithium-ion battery, supercapattery (battery-type electrode), and magnesium rechargeable battery cathodes. A detailed account of the research undertaken is presented herewith and identifies opportunities and research gaps, which are expected to serve as a guide for future research in ternary metal cobaltites. Highlights: Charge storage comparison of MgCo2 O4 with other ternary metal cobaltites. Material chemistry of MgCo2 O4 for energy storage applications. Performance evaluation of MgCo2 O4 as an electrode material for different applications. Future research perspectives in MgCo2 O4 as an energy storage material.